235k views
3 votes
Simplify each expression by using the distributive property and combining like terms. 3 (2x - 4) - 4x

1 Answer

6 votes

Given:

The expression is


3(2x-4)-4x

To find:

The simplified form of the given expression by using the distributive property and combining like terms.

Solution:

We have,


3(2x-4)-4x

Using the distributive property, we get


=3(2x)+3(-4)-4x


=6x-12-4x

On combining like terms, we get


=(6x-4x)-12


=2x-12

Therefore, the simplified form of the given expression is
2x-12.

User Drootang
by
5.0k points